Gentrification as part of urban development - Wrona, Aleksandra (Gentryfikacja jako element rozwoju miast, 2020)
The main purpose of the research was to present gentrification as a diverse phenomenon that cannot be explicitly qualified as negative or positive. In order to illustrate the problem, literature studies were carried out regarding urban regeneration, urban revitalization, gentrification and urban development. Then a case study was presented indicating two extremely different examples. The Walnut Hills Estate in Cincinnati in the United States, was the first to be described. The second example is Sayingmen, which used to be a settlement in Beijing. Due to the controversial decision of the authorities, it was demolished. A discovery resulting from this analysis was to show the diametrically different approach to city management, the perception of civil rights and the scope of competences of local authorities. The case study presented in the article can help institutions related to the development and participatory spatial planning to create urban policies
Biblioteka Regionalisty, 2020, Nr 20, s. 194-202
Keywords: gentrification; sustainable development; urban development; unsustainable development; urban regeneration; urban revitalization; gentryfikacja; zrównoważony rozwój; rozwój miast